Pemikiran Hermeneutika Hasan Hanafi: Sebuah Pendekatan untuk Memahami Islam dan Modernitas - Harianto, Budi; Zulkarnaen, Zulkarnaen; Arifinsyah, Arifinsyah (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2025)
This study explores Hasan Hanafi’s hermeneutics as a contemporary approach to interpreting Islam in response to the challenges of modernity. The rapid development of modern social, political, and cultural dynamics requires an interpretive methodology that goes beyond textual literalism and emphasizes contextual understanding. Hasan Hanafi develops a critical emancipatory hermeneutics that positions human beings as active subjects in interpreting revelation, integrating Islamic intellectual tradition, phenomenology, Marxism, and Western hermeneutics. His hermeneutical framework is built through three levels of consciousness historical, eidetic, and practical aimed at transforming religious texts into a source of social liberation and renewal. This research employs a qualitative method through literature study to analyze Hanafi’s ideas comprehensively. The findings indicate that Hanafi’s hermeneutics serves 006Eot only as a way to understand the text, but also as a transformative paradigm that bridges Islamic tradition with modernity, offering relevant solutions to contemporary issues faced by the Muslim world.